2017
DOI: 10.1111/jir.12376
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models for identifying adults with intellectual disabilities and mealtime support needs who are at greatest risk of respiratory infection and emergency hospitalisation

Abstract: BackgroundAmong adults with intellectual disabilities (ID), problems with eating, drinking and swallowing (EDS), and an associated need for mealtime support, are common, with an estimated 15% of adults known to specialist ID services requiring mealtime support. We set out to identify which adults with ID who receive mealtime support are at an increased risk of respiratory infections and emergency hospitalisation related to EDS problems.MethodAn exploratory, prospective cohort study was undertaken in the East o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This area is diverse, comprising variations in affluence and deprivation as well as urban and rural settings. There are an estimated 174 providers in community residential services in this region, for a total population of 5,383 persons known to specialist services, of whom 142 took part in an exploratory, prospective cohort study of adults identified as needing assistance with eating and drinking (Perez et al., 2017). DSS were eligible for inclusion if they had provided mealtime support to an adult with an intellectual disability who had taken part in an earlier study to estimate the extent and nature of such support (Ball et al., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…This area is diverse, comprising variations in affluence and deprivation as well as urban and rural settings. There are an estimated 174 providers in community residential services in this region, for a total population of 5,383 persons known to specialist services, of whom 142 took part in an exploratory, prospective cohort study of adults identified as needing assistance with eating and drinking (Perez et al., 2017). DSS were eligible for inclusion if they had provided mealtime support to an adult with an intellectual disability who had taken part in an earlier study to estimate the extent and nature of such support (Ball et al., 2012).…”
Section: Methodsmentioning
confidence: 99%